NEW INTERPRETATIONS OF TEACHING IN MOTHER TONGUE SECONDARY SCHOOLS - Xotamova Lobar Shukrillayevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: At present, care over state languages (means Uzbek language). in our country is growing. Therefore, the need for teachers to use new methods, advanced pedagogical and innovative technologies in teaching the subject of mother tongue in order to teach in secondary schools is becoming a modern requirement. It is with this goal in mind that we have dedicated the article to new interpretations of lessons in secondary school mother tongue classes.